Effect of polypropylene fibers on bond performance of reinforcing bars in high strength concrete. (10th August 2019) - Mohebi, Z.H.; Bahnamiri, A.B.; Dehestani, M.
Highlights: Effect of PP fibers on bond behavior in high strength concrete using splice specimens. Failure of splice specimens is brittle and sudden with side and bottom concrete splitting. Failure deflections of splice FRC specimens are 20% higher than plain concrete specimens. The slope of the bond-slip curves of specimens experiences a sudden change at cracking load. No improvement in Pullout bond behavior is observed by adding polypropylene fibers. Abstract: Adequate bonding between reinforcement and concrete plays a vital role in the proper performance of reinforced concrete as a composite material. Hence it is important to evaluate the influence of various factors on the bond behavior of reinforcement and concrete. In this study, a total of 8 beam specimens with tension lap splice at the midspan and 12 concentric pullout specimens are fabricated to investigate the effect of polypropylene fibers on bond performance of reinforcement in high strength concrete (HSC). Fibers are added to concrete mixture by 0.15%, 0.30% and 0.45% volume fraction of concrete. The detrimental effect of polypropylene fiber on the workability of mixture restricts the use of a high amount of polypropylene fiber in mixtures. Splice specimens made of fiber reinforced concrete presented a greater number of cracks, higher failure loads and deflections and also larger crack width at their failure stage. Failure deflections of splice specimens made of fiber reinforced concrete are 20% higher than that of plain concrete specimens on average. After splitting failure, load carrying capacity of all beam specimens dropped to almost zero and the addition of polypropylene fibers did not provide residual capacity for the specimens. The slope of the bond stress-slip curves of specimens experiences a sudden change at the cracking load. Results indicate that existing prediction equations for bond strength are acceptable and even yield more accurate values when polypropylene fibers are added to concrete mixtures. The results of beam and pullout tests demonstrated that pullout test is not suitable to evaluate the effect of polypropylene fibers on bond strength.